2021
DOI: 10.1016/j.ijid.2021.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Leishmania IgG is a marker of disseminated leishmaniasis caused by Leishmania braziliensis

Abstract: Background: In this study, we determined the accuracy of anti-Leishmania IgG and IgG subclasses to distinguish clinical forms of American tegumentary leishmaniasis (ATL) and and determined the relationship between antibodies levels with cytokine production and severity of ATL. Methods: Participants were 40 patients with cutaneous leishmaniasis (CL), 20 patients with mucosal leishmaniasis (ML), 20 patients with disseminated leishmaniasis (DL), and 20 individuals with subclinical Leishmania braziliensis infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…In patients with VL, increased levels of circulating IFNγ regularly accompany progressive infections as also cure, and was reflected in raised IgG2 and IgG4 at disease presentation and cure [ 17 , 25 , 39 ]. A similar scenario was reported in Disseminated Leishmaniasis wherein high levels of IFNγ were accompanied by an increased IgG2, and importantly, was an effective predictor of disease [ 51 ]. At disease presentation, the raised IFNγ reported in human VL [ 21 , 52 , 53 ], CL [ 54 ], and PKDL [ 21 , 41 ] indicates a mixed Th1/Th2 milieu, the latter being predominant [ 20 22 ]).…”
Section: Discussionsupporting
confidence: 63%
“…In patients with VL, increased levels of circulating IFNγ regularly accompany progressive infections as also cure, and was reflected in raised IgG2 and IgG4 at disease presentation and cure [ 17 , 25 , 39 ]. A similar scenario was reported in Disseminated Leishmaniasis wherein high levels of IFNγ were accompanied by an increased IgG2, and importantly, was an effective predictor of disease [ 51 ]. At disease presentation, the raised IFNγ reported in human VL [ 21 , 52 , 53 ], CL [ 54 ], and PKDL [ 21 , 41 ] indicates a mixed Th1/Th2 milieu, the latter being predominant [ 20 22 ]).…”
Section: Discussionsupporting
confidence: 63%
“…Seropositivity rates and antibody titers were higher among people with multiple lesions (100.0%) compared to those with single lesions (90.2%; p < 0.05). A similar finding was observed among patients with multiple CL lesions caused by L. tropica (Wright, 1903) [ 37 , 38 ], and anti- Leishmania IgG2 was shown to be directly correlated to the number of lesions in patients with diffuse cutaneous leishmaniasis caused by L. braziliensis (Vianna, 1911) [ 39 , 40 ]. Multiple lesions could be due to multiple inoculating bites by the vector.…”
Section: Discussionsupporting
confidence: 60%
“…Higher levels of total anti-leishmanial IgG and IgG subclasses have also been associated with active disease 32 as well as severity of disease. 33 Moreover, some studies have demonstrated the presence of IgG antibodies as an indicator of disease progression of CL infection. 26,[34][35][36] A shift to relatively low antibody levels, which happened earlier in the patients under treatment in our study population, suggests that the decrease in antibody levels may be a marker of the therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the antibody levels remained high for an extended period of time in untreated patients, which is likely to be due to higher parasite antigenic stimulation in this group. Higher levels of total anti‐leishmanial IgG and IgG subclasses have also been associated with active disease 32 as well as severity of disease 33 . Moreover, some studies have demonstrated the presence of IgG antibodies as an indicator of disease progression of CL infection 26,34–36 .…”
Section: Discussionmentioning
confidence: 99%